Functional Outcome of Intramedullary Kirschner Wire Fixation of Unstable Radius-Ulna Fractures in Children: Intramedullary Kirschner Wire Fixation of Unstable Radius-Ulna Fractures - Khan, Imran; Khan, Alamzeb; Khan, Mudir; Rasool, Muhammad; Hamid, Abdul; Ullah, Saeed (Pakistan Journal of Health Sciences, 2023)
Pediatric patients with unstable radius-ulna fracture can be treated with intramedullary Kirschner wire fixation. Objective: To determine the functional outcome of Intramedullary Kirschner Wire fixation in unstable radius-ulna fractures in children. Methods: All pediatric age patients were enrolled into the study with unstable radius and ulna fracture. Informed consent was taken before study. Proper history, examination and X-rays of the forearm was taken after taking consent from the guardian of the patient. Under general anesthesia and tourniquet, control radius was first fixed through a small volar incision by drilling a k wire at fracture site in radius so that the wire exits on the dorsolateral side of the radius. The fracture was than reduced and the wire tapped with hammer to the radial head. Similarly, ulna was fixed by first drilling the wire up to the olecranon process and after reduction of the fracture down to the styloid process. After checking stability both bones, both wounds were washed with normal saline and closed in reverse order and above elbow cast was applied for three to four weeks. Results: In this study, as per functional outcomes, 5(4.0%) patients had good outcome, 80(64%) patients had excellent outcomes whereas 40(32%) patients had poor outcomes. Conclusions: This study demonstrates excellent functional outcome of Intramedullary Kirschner Wire fixation in unstable both bone forearm fractures in children.